PREDIKSI WAKTU SPAWNING KARANG ACROPORA PADA MUSIM PERALIHAN KEDUA DI PULAU SAMBANGAN KEPULAUAN KARIMUNJAWA JEPARA - Komarudin, Agus Nurul; Munasik, Munasik; Marwoto, Jarot (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Knowledge of coral reproduction in Indonesian waters were divided into three groups, there are the spawning time which occurs in first transition season or before East season (January to April), the spawning time which occurs in second transition season or before West season (September-November), and the spawning time which occurs throughout the year. This study aims to predicted spawning time of Acropora by observe gonad maturity level during second transition season (September-October 2012) at Sambangan Island Karimunjawa Archipelago Jepara. The method used in this research was descriptive method. Distribution and composition Acropora were observed using Line Intercept Transect (LIT) method. Spawning time of Acropora was determined by presence or absence of gonad contents, and the maturity level of the gonads deferred to Hanafy et al. (2009). Gonad was examine in new moon phase, before full moon phase, and after full moon phase. The result show that distribution and composition of coral species Acropora at Sambangan Island in depth of 1-3 m was known 5 species of the stations I, 6 species at station II, and 8 species at station III with the highest cover composition at each station was a species A. formosa. Total 8 species Acropora were observe however only two species were found content of gonad. There were Acropora carduus and A. formosa. The gonad of coral A. carduus matured earlier than A. formosa. Gonad maturity of A. carduus occurred in September 2012 (new moon) and then gonad didn’t found in the phase before the full moon. Gonad maturity of coral A. formosa occured on the full moon phase in October 2012 and the phase after full moon the colony hadn’t contain gonads. Based on this information spawning of two species of Acropora likely occurred in different moon phase. Species of A. carduus has been spawned before the full moon phase and species A. formosa has been doing spawning after the full moon phase in October 2012.